Saúde mental e as estratégias de enfrentamento das mulheres pescadoras diante das situações de crise - Silva, Francisca Rachel da (2023)
Health undergoes through several transformations, from the differentiation between what is health and disease, to the development of new fields of study in the area. These fields shed light on understanding the processes of contexts such as those of traditional communities and their confrontations, as well as the possibility of developing public policies aimed at them. Fisherwomen face challenges against social issues that permeate being a woman, in addition to experiencing crises within their field of work that stress their mental health, such as those discussed here: the oil spill and the pandemic of COVID-19. Therefore, this study sought out to understand the impact of some crisis situations on the mental health of fisherwomen and their respective coping strategies. Characterizing the lifestyle and work of fisherwomen, describing some impacts of crisis scenarios on their mental health and identifying their own coping strategies. The research is a qualitative, descriptive, collaborative non-extractive study and was carried out in the traditional communities of Sítio Jardins, Quilombo do Cumbe and Canavieiras. Observation, interviews or general verbal interactions and field diaries were used to obtain data. To analyze them the field of discourse analysis. The results of the study made it possible to understand some significant and authentic characteristics of each community, certain experiences, copings and the importance of community associations. It was also possible, as a direction from this research, a brief articulation example of the health care network in a horizontal, collaborative and systemic way that favored the description of a knowleadges meeting sui generis in the context of fisherwomen located in traditional communities.